2018
DOI: 10.3389/fgene.2018.00452
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Rhythms and Mitochondria: Connecting the Dots

Abstract: Circadian rhythms provide a selective advantage by anticipating organismal nutrient needs and guaranteeing optimal metabolic capacity during active hours. Impairment of circadian rhythms is associated with increased risk of type 2 diabetes and emerging evidence suggests that metabolic diseases are linked to perturbed clock machinery. The circadian clock regulates many transcriptional–translational processes influencing whole cell metabolism and particularly mitochondrial activity. In this review, we survey the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 76 publications
(55 citation statements)
references
References 65 publications
(91 reference statements)
1
54
0
Order By: Relevance
“…It has been reported that AMPK and SIRT1 participate in the circadian network. [ 37–39 ] Our results were consistent with the results of Nakahata et al., AMPK phosphorylation activity and SIRT1 deacetylation activity showed diurnal rhythm in CON mice. [ 40,49,50 ] SR did change the activity preferences in mice which interacted with the activity of AMPK and SIRT1.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…It has been reported that AMPK and SIRT1 participate in the circadian network. [ 37–39 ] Our results were consistent with the results of Nakahata et al., AMPK phosphorylation activity and SIRT1 deacetylation activity showed diurnal rhythm in CON mice. [ 40,49,50 ] SR did change the activity preferences in mice which interacted with the activity of AMPK and SIRT1.…”
Section: Discussionsupporting
confidence: 92%
“…And there was substantial evidence that AMPK and SIRT1 were involved, and even directly regulate clock mechanisms. [ 37–39 ] It has been confirmed that phosphorylation activity of AMPK and deacetylation activity of SIRT1 actually are involved in regulation of circadian rhythms. [ 40,41 ] Therefore, we further tested the activity of AMPK and SIRT1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Altered mitochondrial activity in dfrm1 was demonstrated through elevated levels of maximum electron transport system in isolated mitochondria and marked mitochondrial abnormalities in flight muscles. While altered mitochondrial activity in per 01 flies has already been suggested by increased mitochondrial hydroperoxyde levels [12] and evidence for a tight circadian control of mitochondrial dynamics and functions is steadily growing in mammals [71,72], it is clear that further and especially mechanistic studies are required to corroborate the idea of an altered mitochondrial activity in Drosophila. Notwithstanding, our results now provide a basis to employ the genetic power of Drosophila to identify the still largely unknown mechanisms underlying the circadian control of metabolism.…”
Section: Several Lines Of Evidence Point Towards Altered Mitochondriamentioning
confidence: 99%
“…Mitochondria are therefore highly dynamic, and their activity varies according to the cell's nutritional status at different times of the day [ 14 , 15 ]. This flexibility is supposed to be achieved through some possible crosstalk mechanisms between mitochondrial functions and circadian clocks [ [16] , [17] , [18] , [19] , [20] ]. Mitochondria also generate much of the cellular reactive oxygen species (ROS) as a by-product within most mammalian cells [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%